Demand side management: energy efficiency (lighting system) in PTAR 1/ Nazri Nordin - Nordin, Nazri (1997)
Energy efficiency is important for improving the power consumption of any building or factory. Energy efficiency is increasingly becoming more important due to the increasing in costs of electrical energies. The advance developments in the technology in producing devices and products that can save energy enhance energy efficiency applications in the existing building. This report summarised the result of the energy efficiency study perform for the Perpustakaan Tun Razakl (PTAR l), main campus, Mara Institute of Technology, Shah Alam Selangor Darul Ehsan. The primary concern is on upgrading the existing lighting system in the PTAR l. The studied of the facility of the PTAR l building were made and the opportunity for improving the energy efficiency facility and reducing the energy consumption were identified and evaluated. The economic analyse has also been calculated in order to determined the cost effectiveness. The facility that has pay back period not exceeding its life spends will be recommended for installation.